Pesticide Exposure and Increased Liver Enzyme Activity among Suburban Horticultural - Dahlan, Ahmad; Simanjuntak, James Perdinan; Mustopa, Raden; Putri, Devi Oktarina; Amanda, Putrilia; Ratri, Adinda Cahyaning; Syathibi, Ahmad; Sabarudin, Sabarudin; Haflin, Haflin (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
Horticultural farmers use chemicals such as pesticides to increase productivity and product quality. Exposure to pesticides can cause health problems, especially in the liver. A reference for evaluating liver function is blood test results for ALT, AST, ALP, and GGT activity. This study aimed to characterize the transaminase enzyme activity in horticultural farmers in the southern ring road area of Jambi City based on the risk factors associated with pesticide exposure. This study employed a cross-sectional study approach in conjunction with a descriptive method. Thirty-four participants were involved, and blood samples were obtained from each for analysis in a lab. A photometer was utilized in the Medical Laboratory Technology department at Health Polytechnic of Jambi to measure the activity of liver enzymes. This study found some respondents who experienced increased enzyme activity, namely ALT: 8 people (23.5%), AST: 3 people (8.8%), ALP: 1 person (2.9%), and GGT: 1 person (2.9%.). Based on the risk description observed, it was known that the intensity of pesticide exposure showed a significant increase only in ALT enzyme activity (p=0.0048), while adherence to mask-wearing increased ALT (p=0.0018) and GGT (p=0.0134). This study discovered that wearing a mask and the amount of pesticide exposure can increase enzyme activity, which may indicate liver impairment in the horticultural farmers under observation. Workers are expected to pay greater attention to workplace safety by wearing masks and applying pesticides in the recommended dosages.